Ability of Swept-Source Optical Coherence Tomography to Detect Retinal and Choroidal Changes in Patients with Multiple Sclerosis. (13th November 2018) - Garcia-Martin, Elena; Jarauta, Laura; Vilades, Elisa; Ara, Jose Ramon; Martin, Jesus; Polo, Vicente; Larrosa, Jose Manuel; Pablo, Luis Emilio; Satue, Maria
Abstract : Purpose . To evaluate the ability of new swept-source (SS) optical coherence tomography (OCT) technology to detect changes in retinal and choroidal thickness in patients with multiple sclerosis (MS). Methods . A total of 101 healthy and 97 MS eyes underwent retinal and choroidal assessment using SS Triton OCT (Topcon). Macular thickness and peripapillary data (retinal, ganglion cell layer (GCL+, GCL++) and retinal nerve fiber layer (RNFL) thickness) were analyzed, including choroidal thickness evaluation. Results . Significant macular thinning was observed in all ETDRS areas (p < 0.001 ) in MS patients. Peripapillary retinal, RNFL, and GCL ++ thickness showed a significant reduction in patients in all sectors (p < 0.001 ) except in the nasal quadrant/sector (p > 0.05 ). GCL+ measurements were found to be reduced in the nasal (p = 0.003 ), inferonasal (p = 0.045 ), and temporal (p = 0.001 ) sectors and total thickness (p < 0.001 ). Choroidal thickness was reduced in the outer macular ring in MS patients compared with controls (p = 0.038 ). Conclusion . New swept-source technology for OCT devices detects retinal thinning in MS patients, providing increased depth analysis of the choroid in these patients. MS patients present reduced retinal and choroidal thickness in the macular area and reduced peripapillary retinal, RNFL, and GCL thickness.